A novel control strategy for mode seamless switching of PV converter in DC microgrid based on double integral sliding mode control. (May 2020) - Zhang, Qinjin; Zhuang, Xuzhou; Liu, Yancheng; Wang, Chuan; Guo, Hongzhi
Abstract: With the photovoltaic (PV) penetration increases in dc microgrid, the traditional PV converters with maximum power point tracking (MPPT) control, which are equivalent to current sources, can hardly meet the needs of coordinated operation. The PV converter should operate in both MPPT and constant voltage control (CVC) modes. When the operation mode changes, the PV converter needs to switch between current and voltage sources. Inevitably, the bus voltage instability would be caused. This paper presents a novel switching strategy for the smooth and seamless operation of the PV converter between MPPT and CVC modes. The PV converter under these two modes is always controlled as a voltage source, and its control variables are both the output voltage of PV arrays. When its operation mode changes from MPPT to CVC, a small offset signal based on DC bus voltage would be introduced to the reference voltage of inner loop of the PV converter, so as to shift the maximum power point (MPP) voltage. Meanwhile in the voltage inner loop, a double integral sliding mode controller (DISMC) is used to improve the performance and anti-interference ability of the PV converter. This method unifies MPPT and bus voltage adjustment strategy without any communication and changing any hardware structure and control parameters. When mode switching occurs, only the reference value of voltage inner loop would be slightly adjusted near the maximum photovoltaic power point, so the seamless transition for PV converter between the two modes can be ensured. Finally, the effectiveness of the mode seamless switching control strategy is demonstrated by the simulation and experimental tests. Highlights: Double integral sliding mode control is proposed for one-stage PV converter. Small offset signal based on bus voltage is adopted to adjust PV working voltage. PV converter under MPPT and CVC modes is always controlled as voltage source. Parameter setting method of seamless switching controller is analyzed in detail. Seamless transition for PV converter between MPPT and CVC modes is realized.